مياه نهر دجلة أمام سدة الكوت وأثرها على البنى التحتية في مدينة الكوت - عذاب خليف الموسوي حسين; راضي حسين القريشي ماجد (Journal of College of Education, 2019)
Water of Tigris River of Kut Dam and Effect on the Subsurface Building in Kut City The high levels of water of the Tigris River have a great impact on the infrastructure and buildings, especially in front of the Kut dam, which greatly affects the high porosity of the soil of the levees of the Tigris river and also of the poetic property, the role of the leakage of large amounts of water to the residential neighborhoods in the center of the city of Kut, Tigris in front of the dam, such as the revival of (Hoora - Malmeen - Cafaat - Kalej), influenced by the physical and chemical weathering processes. The physical weathering was characterized by wetting and drying during the fall of rain on the walls of buildings in the length of rainfall in large quantities and drought during high temperatures, which leads to the emergence of white salts on the walls as this phenomenon known (salinity bloom) and repeat this process several times starting these walls distortion and exposure to scraping or separation of the outer shell of the building material (bricks). The chemical weathering is characterized by erosion, which is affected by the subsurface structures such as the foundations of buildings, especially the buildings that used limestone or soluble gaseous material in the groundwater that leaked through the natural levees towards the low areas next to the Tigris River. Lead to affect the foundations of buildings and streets in those neighborhoods and these effects are the phenomenon of subsidence in buildings and streets .